Global research status and trends of enteric glia: a bibliometric analysis - Li, Huai-Yu; Yan, Wei-Xin; Li, Jia; Ye, Jing; Wu, Zhi-Guo; Hou, Zheng-Kun; Chen, Bin (Frontiers in Pharmacology, 2024)
Background: Enteric glia are essential components of the enteric nervous system. Previously believed to have a passive structural function, mounting evidence now suggests that these cells are indispensable for maintaining gastrointestinal homeostasis and exert pivotal influences on both well-being and pathological conditions. This study aimed to investigate the global status, research hotspots, and future directions of enteric glia. Methods: The literature on enteric glia research was acquired from the Web of Science Core Collection. VOSviewer software (v1.6.19) was employed to visually represent co-operation networks among countries, institutions, and authors. The co-occurrence analysis of keywords and co-citation analysis of references were conducted using CiteSpace (v6.1.R6). Simultaneously, cluster analysis and burst detection of keywords and references were performed. Results: A total of 514 publications from 36 countries were reviewed. The United States was identified as the most influential country. The top-ranked institutions were University of Nantes and Michigan State University. Michel Neunlist was the most cited author. “Purinergic signaling” was the largest co-cited reference cluster, while “enteric glial cells (EGCs)” was the cluster with the highest number of co-occurring keywords. As the keyword with the highest burst strength, Crohns disease was a hot topic in the early research on enteric glia. The burst detection of keywords revealed that inflammation, intestinal motility, and gut microbiota may be the research frontiers. Conclusion: This study provides a comprehensive bibliometric analysis of enteric glia research. EGCs have emerged as a crucial link between neurons and immune cells, attracting significant research attention in neurogastroenterology. Their fundamental and translational studies on inflammation, intestinal motility, and gut microbiota may promote the treatment of some gastrointestinal and parenteral disorders.